Exploring Religious Moderation Practices Among Mosque Imams in Dairi Regency Through Local Wisdom and Health Mentality - Ponidi Ponidi; Fitri Hayati; Putri Safira; Prima Yanti Siregar; Apriliani Apriliani; Muhammad Rezebri (Contagion: Scientific Periodical Journal of Public Health and Coastal Health, 2024)
Introduction: In pluralistic societies like Indonesia, religious moderation is a critical public health and social cohesion imperative. Mosques and their imams serve as pivotal institutions and leaders in shaping community attitudes. This study explores how mosque imams in the Muslim-minority regions of Dairy and West Pakpak, North Sumatra, leverage local wisdom to foster religious moderation and social harmony.Objective: This research aims to analyze the practices and impact of mosque imams in promoting religious moderation by integrating Islamic teachings with indigenous local values, specifically the Sikata One (unity and solidarity) and Marga Silima (balance and harmony) principles of the Pakpak community.Methods: A qualitative study was conducted in Dairy and West Pakpak Regencies. Data were collected through in-depth interviews with mosque imams and administrators (n=40) and supplemented by content analysis of relevant documents, including local manuscripts and literature on religious moderation. A thematic analysis was employed to identify key patterns in the imams' strategies for integrating local wisdom with religious teachings.Results: The findings reveal a high prevalence of moderate attitudes among community members influenced by the imams. Key results include: 70% acceptance of friends from different religions; 75% rejection of coercing others to conform to one's religious will; and 90% comfort in sitting next to individuals of different faiths at events. Thematic analysis identified that imams actively incorporate the principles of Sikata One and Marga Silima into sermons and community guidance, framing religious coexistence as an extension of traditional cultural values.Conclusion: Mosque imams play an instrumental role as agents of religious moderation by effectively syncretizing Islamic doctrine with deeply held local wisdom. This culturally-grounded approach, championed by religious leaders, is a significant factor in the sustained interfaith harmony observed in these regions. The study underscores the importance of leveraging cultural assets and religious leadership in public health and policy initiatives aimed at building resilient, tolerant, and cohesive societies. Keywords: Religious Moderation, Mosque Imams, Local Wisdom, Social Cohesion.